Evaluation of hepatoprotective effects and bioactivities of Phyllanthus Niruri and Melastoma Malabathricum / Zahra Abdulqader Amin - Zahra, Abdulqader Amin (2013)

(untitled)
The liver plays an essential role in the body by regulating several important metabolic functions. Liver injury is associated with distortion of these functions causing many health problems. Pharmaceutical drugs treat liver disorders but carry the risk of causing further damage to the liver. Hence, herbal drugs have been becoming increasingly popular worldwide as both patients and doctors strive to find safer alternatives. The bioactivities of the crude ethanol extracts of Phyllnthus niruri L. (PN) and Melastoma malabathricum L. (MM) were investigated in virtue of their in vitro antioxidant, immunomodulatory effects and in vivo oral toxicity tests. The hepatoprotective activity was evaluated against thioacetamide (TAA) induced liver cirrhosis in rats. Antioxidant activity was evaluated by different assays, including: 2,2-diphenlyl-1-picrylhydrazyl (DPPH), 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activities and ferric reducing antioxidant power (FRAP). Total phenolic content (TPC) and total flavonoids content (TFC) of the plants extracts were also determined. The immunomodulatory effect was studied on human peripheral mononuclear cells (PBMC) by 3-(4,5-dimethylthiazol-2-yl)-2‚5-diphenyltetrazolium bromide (MTT) assay. To induce liver injury, male Sprague Dawley rats were administered by intraperitoneal injections (i.p.) of thioacetamide (TAA, 200 mg/kg, b.w. thrice weekly) for eight weeks to assess the hepatoprotective effect of the extracts. Daily treatments with plant extracts 100 mg/kg b.w., 200 mg/kg and silymarin (50 mg/kg) administered orally were carried out for eight weeks. At the end of the study, hepatic damage was evaluated by monitoring liver‘s gross morphology, histopathology, weight changes, biochemical parameters, endogenous antioxidants activities including total antioxidant capacity (TAC), catalase (CAT), ii superoxide dismutase (SOD), glutathione peroxidase (GPX) and malondialdehyde (MDA) in the liver homogenates. Gene expressions were also studied by profiling transforming growth factor (TGFβ1), collagen α1 (Collα1), matrix metalloproteinase-2 (MMP2) and tissue inhibitor of metalloproteinase-1 (TIMP1) by Real Time PCR. Besides, different chromatography techniques were used to isolate the active constituents of the plants including column chromatography, thin layer chromatography and ultra performance liquid chromatography (UPLC) with liquid chromatography coupled to mass spectrometry (LC-MS). Our results revealed that treatment with 200 mg/kg of PN and MM significantly reduced the impact of thioacetamide toxicity and they were effectively hepatoprotective, comparable to that of silymarin. The mechanism of the hepatoprotective effects of PN and MM, proposed to be through neutralizing the reactive oxygen species (ROS) and enhancement of endogenous antioxidant activities SOD, GPX and suppression of oxidative stress marker MDA. Additionally, PN and MM treatment normalized the expression of TGFβ, Collα1, MMP2 and TIMP1 genes. The isolated chemical constituents included in P. niruri were 4-O-caffeolquinic acid and quercetin 3-O-rhamnoside while in M. malabathricum were kaempferol, quercetin and naringenin. In conclusion, the results of the present study indicate that PN and MM ethanol extracts were hepatoprotective and toxicologically safe when administered orally. We postulated that the hepatoprotective effect of these extracts might be in part due to the active components, antioxidant and immunomodulatory properties.